Comparative analysis of herbal and synthetic hormone on super male tilapia production - Mazzaellynn Brasenia Umang, Thomas Inau (Universiti Malaysia Sarawak (UNIMAS), 2022)
Oreochromis niloticus is one of the commercial species that plays important role in global production of fisheries especially in economic sectors. The Nile Tilapia, Oreochromis niloticus was studied to enhance the growth population especially the males tilapia for economics and instead of using synthetic hormone which is 17-methyl testosterone that typically been used years for sex reversal, this study which has been done in Honey Aquaculture Lab was tried to develop using natural sources which is 10 Chinese traditional herbs. The 10 Chinese traditional herbs are Sigesbeckia orientalis, Codonopsis pilosula, Citrus aurantium, Aquilaria sinensis, Cistanche deserticola, Commiphora myrrha, Fen caopo, Juglans nigra, Citrus sinensis, and Ligusticum chuanxiong Hort. These herbs then mixed with hand-made formulated fish feed consisting 40% protein and 6% lipid and fed to the fries of tilapia which known as F0 generation. There were 2000 wild tilapia parents obtained from Sungai Batang Kali. This study continuously monitored until the tilapia itself breed. The growth of performance of the tilapia will also be monitored from its rearing days after hatching. The measurement involves using Independent T-Test which measured the length and weight of the two dose and 3 replicates been done.